Ekonomska analiza sprejetja Uredbe o skupnem evropskem prodajnem pravu - Geč, Tjaša (Podjetje in delo, 2016)
Taking into account both positive and negative reviews of the Common European Sales Law, the primary purpose of this paper is to analyse what its adoption and use would mean for the most cost-effective and desired (cross-border) transactions. Despite the fact that the proposal has been withdrawn from the list of legislative proposals contained in the European Commission's 2015 work programme, this optional instrument remains relevant for consideration, since it can serve as a reference model for a new proposal that will form a part of an ambitious legislation for the Digital Single Market. The first part focuses on the current European Sales Law, which - due to differences in contract law between Member States - does not reach the full potential of the single market of 500 million consumers. It also sets out the main obstacles related to the cost functions of enterprises which dissuade them from entering foreign markets, and the innovations introduced by the proposed regulation in the field of European Sales Law. The second part concentrates on the cost and benefit analysis of opting into the proposal, and examines corporate behaviour depending on different levels of the European standard of consumer rights. At the conceptual level, revolutionary significance could be attributed to this Regulation, since it brings in the European space the original concept of the Common European Sales Law, which was unthinkable until recently. However, given the competition of contractual regimes at present, it seems to have little chance of implementation. Particularly problematic are the nature and the scope of the instrument, which, contrary to the very purpose of the regulation - to reduce transaction costs and consequently to promote cross-border transactions - increase the costs, thus burdening especially small and medium enterprises.
Keywords: enotni trg; Evropska unija; mednarodna trgovina; pravna ureditev; prodaja